Neonatal Survival and Outcomes following Periviable Rupture of Membranes - Okonek, Elizabeth J.; Schulz, Elizabeth V.; Belzer, Kira; Aden, James K.; Drumm, Caitlin M. (American Journal of Perinatology, 2024)
To clarify survival for infants affected by periviable prolonged preterm premature rupture of membranes (PPROM) in the military health system (MHS). To add to current literature on outcomes following expectant management, including long-term neurodevelopment outcomes.Retrospective matched cohort review of six level 3 military neonatal intensive care units (NICUs; 2010–2020). Cases were matched 1:1 with control infants, matched by location, gender, gestational age (within 1 week), birth weight (within 300 g), and rupture of membranes (ROM) within 24 hours of delivery. Follow-up data were obtained for each infant through 48 months' corrected age or age of last documented health visit in a military treatment facility.Forty-nine infants met inclusion criteria. Mean ROM for cohort infants was 20.7 weeks, with mean latency period of 34.6 days and mean gestational age at delivery of 25.7 weeks. Cohort infants had a mean birth weight of 919 g. Cohort survival to NICU discharge was 75.5 versus 77.6% of controls (p = 0.81). Statistically significant short-term outcomes: oligohydramnios or anhydramnios at delivery (p < 0.0001), pulmonary hypertension (p = 0.0003), and high-frequency ventilation (p = 0.004) were higher in cohort infants. No differences were found regarding rates of early sepsis, intraventricular hemorrhage, surgical necrotizing enterocolitis, oxygen at 36 weeks or at discharge. No statistical difference in long-term outcomes at 18 to 48 months of age or incidence of autism, cerebral palsy, attention deficit hyperactivity disorder, or asthma.Cohort survival to discharge in the MHS was 75.5%, higher than previously reported and not different from matched controls. Infants born after periviable PPROM should deliver at centers with access to high-frequency ventilation and ability to manage pulmonary hypertension. There was no difference in long-term neurodevelopment between the groups.
Keywords: periviable PPROM; NICU survival; neurodevelopmental outcomes